1988
DOI: 10.1093/clinids/10.supplement_1.s153
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Fluoroquinolones in the Treatment of Urinary Tract Infections

Abstract: The resultsof comparative trials of fluoroquinolones for the treatment of uncomplicated and complicated urinary tract infections (UTI) were reviewed. Severalrandomized, comparative trials showedthat in uncomplicated UTI norfloxacin, ciprofloxacin, and ofloxacin wereat least as effectiveas trimethoprim-sulfamethoxazole (TMP-SMZ) and amoxicillinand usually more effectivethan nalidixicacid, pipemidic acid, and nitrofurantoin. Comparativetrials of single-dose regimens have, however, been limited. A few randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…New fluoroquinolones have emerged as effective antimicrobial agents in the treatment of both complicated and non‐complicated urinary tract infections (UTI). Comparative trials by our unit and other centres have recently demonstrated that norfloxacin, ciprofloxacin and ofloxacin 1,2 are at least as efficacious as trimethoprim‐sulfamethoxazole and amoxycillin in the treatment of these infections.…”
Section: Introductionmentioning
confidence: 92%
“…New fluoroquinolones have emerged as effective antimicrobial agents in the treatment of both complicated and non‐complicated urinary tract infections (UTI). Comparative trials by our unit and other centres have recently demonstrated that norfloxacin, ciprofloxacin and ofloxacin 1,2 are at least as efficacious as trimethoprim‐sulfamethoxazole and amoxycillin in the treatment of these infections.…”
Section: Introductionmentioning
confidence: 92%
“…39 ofloxacin 100 mg,40-46 fleroxacin 200, 400, or 600 mg,47-50 and pefloxacin 800 mgsl have been highly effective in women with uncomplicated lower urinary tract infections caused by Enterobacteriaceae, but may be less effective against Staphylococcus saprophyticus. 52 Bact e r i o I og i c c u re rates we re 87% (40/46) for high-dose n o r f l o x a~i n ,~~. 37 82% (59/72) for low-dose c i p r o f l~x a c i n ,~* * 39 80% (1 68/21 1 ) for o f l~x a c i n ,~~-~~ 90% (57/63) for f l e r~x a c i n ,~~-~~ and 83% (55/66) for pefloxa~in.~' The overall bacteriologic cure rate for single-dose quinolone therapy was 83% (379/458), which was at least comparable to that for TMP-SMX and other agents.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%